Graphite, its precursors and methods for their production, negative electrodes and batteries
Patent Information
- Application Number
- CN202410138236.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-01-31
AI Technical Summary
The development of graphite anode materials in the direction of fast charging is limited by their end-face lithium intercalation mechanism, which makes lithium-ion intercalation difficult.
The raw coke powder is treated with a polar organic solvent to dissolve and volatilize the soluble substances in the raw coke powder to form a graphite precursor. Then, it is graphitized at high temperature to form a non-oriented hard carbon thin layer to increase porosity, provide lithium ion insertion channels, and use the raw coke material itself as a coating layer to save costs.
It improves the fast charging performance of graphite, enhances the lithium-ion intercalation channel, increases the charging capacity and capacity retention of graphite, and saves on coating agent costs.
Smart Images

Figure CN120398044B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and more specifically, to graphite, its precursors and their preparation methods, negative electrodes and batteries. Background Technology
[0002] Lithium-ion batteries are widely used in new energy and other fields due to their high energy density and excellent cycle performance. Graphite anode materials are also widely used in lithium batteries due to their high specific capacity, low cost, and environmental friendliness. However, the end-face lithium intercalation mechanism of graphite anodes limits their development in the fast-charging direction.
[0003] In view of this, the present invention is proposed. Summary of the Invention
[0004] The purpose of this invention is to provide graphite, its precursors and methods for their preparation, negative electrodes and batteries, and to improve at least one of the problems mentioned in the background art.
[0005] This invention is implemented as follows:
[0006] In a first aspect, the present invention provides a method for preparing a graphite precursor, comprising:
[0007] The raw coke powder is mixed evenly with a polar organic solvent to fully dissolve the soluble substances in the raw coke powder into the polar organic solvent to obtain a mixture;
[0008] The polar organic solvent in the mixture is evaporated to obtain a graphite precursor.
[0009] In an optional implementation, the F-value of the coke is ≥0.1%;
[0010] Optionally, the raw coke is petroleum coke, needle coke, or pitch coke;
[0011] Optionally, the particle size of the raw coke powder is 1–100 μm.
[0012] In an optional embodiment, the method of fully dissolving the soluble substances in the raw coke powder in a polar organic solvent to obtain a mixture includes:
[0013] The raw coke powder is mixed with a polar organic solvent and then stirred. The stirring time is not particularly limited, as long as the soluble substances in the raw coke powder are fully dissolved in the polar organic solvent. Optionally, the stirring time is 2–6 hours.
[0014] In an optional embodiment, the polar organic solvent is selected from at least one of tetrahydrofuran, toluene, dichloromethane, trichloromethane, and ethyl acetate;
[0015] Optionally, the ratio of raw coke powder to polar organic solvent is 1 kg: 1 to 5 L. Specifically, the ratio of raw coke powder to organic solvent is 1 kg: 1 L, 2 L, 3 L, 4 L, or 5 L. The raw coke powder only needs to be uniformly dispersed in the organic solvent; there are no particular limitations.
[0016] In an optional embodiment, the method of evaporating the polar organic solvent in the mixture includes:
[0017] The mixture is dried at 80–120°C. The appropriate temperature is selected based on the boiling point of the organic solvent used, and there is no particular limitation. For example, when using tetrahydrofuran or dichloromethane, which have lower boiling points, as solvents, drying at 80°C is sufficient; while when using toluene, which has a higher boiling point, as solvent, drying at 120°C is recommended.
[0018] Alternatively, the mixture can be first subjected to rotary evaporation to recover the polar organic solvent, and then dried at 80–120°C.
[0019] Secondly, the present invention provides a graphite precursor, which is prepared by any of the preparation methods described in the foregoing embodiments.
[0020] Thirdly, the present invention provides a method for preparing graphite, wherein the graphite precursor as described in the foregoing embodiments is graphitized; optionally, the graphitization temperature is 2900–3100°C.
[0021] Fourthly, the present invention provides a method for preparing graphite, comprising:
[0022] The raw coke powder is mixed evenly with a polar organic solvent to fully dissolve the soluble substances in the raw coke powder into the polar organic solvent to obtain a mixture;
[0023] The polar organic solvent in the mixture is evaporated to obtain a graphite precursor;
[0024] The graphite precursor is subjected to graphitization treatment. Optionally, the graphitization temperature is 2900–3100°C.
[0025] Before graphitization, it can be treated by grading, modification or granulation. After graphitization, it can be treated by modification, coating or granulation.
[0026] Fifthly, the present invention provides a graphite prepared by the preparation method described in the foregoing embodiments.
[0027] In a sixth aspect, the present invention provides a negative electrode made of graphite as described in the foregoing embodiments.
[0028] In a seventh aspect, the present invention provides a battery including a negative electrode as described in the foregoing embodiments.
[0029] The present invention has the following beneficial effects:
[0030] The method for preparing graphite precursors involves treating raw coke powder with a polar organic solvent. This extracts small molecules from the raw coke that are soluble in the solvent. After the solvent evaporates, these small molecules are loaded onto the outside of the raw coke particles. This precursor is then used to prepare graphite. The small molecules on the precursor surface are carbonized at high temperature into a non-oriented, porous hard carbon layer. This results in a more porous graphite surface, providing ample channels for lithium-ion intercalation and effectively improving the fast-charging performance of the graphite. Furthermore, the coating material in this method is derived from the raw coke itself, achieving "self-sufficiency" and saving on coating agent costs. Attached Figure Description
[0031] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 A process flow diagram of the technical solution provided by the present invention. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0034] The following provides a detailed description of the graphite, its precursor, its preparation method, negative electrode, and battery provided in the embodiments of the present invention.
[0035] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a graphite precursor, comprising:
[0036] The raw coke powder is mixed evenly with a polar organic solvent to fully dissolve the soluble substances in the raw coke powder into the polar organic solvent to obtain a mixture;
[0037] The polar organic solvent in the mixture is evaporated to obtain the graphite precursor.
[0038] The method for preparing a graphite precursor provided in this invention involves treating raw coke powder with a polar organic solvent. This extracts small molecules from the raw coke that are soluble in the solvent. After the solvent evaporates, these small molecules are loaded onto the outside of the raw coke particles. This precursor is then used to prepare graphite. The small molecules on the surface of the precursor are carbonized at high temperature to form a non-oriented, porous hard carbon layer. This results in a graphite surface with more pores, providing ample channels for lithium-ion intercalation and effectively improving the fast-charging performance of the graphite. Furthermore, the coating material in this method is derived from the raw coke itself, achieving "self-sufficiency" and saving on coating agent costs.
[0039] Therefore, the graphite precursor prepared by the method provided in this embodiment of the invention has better fast-charging performance than untreated raw coke powder when used to prepare graphite.
[0040] Optionally, the method of fully dissolving the soluble substances in the raw coke powder into the polar organic solvent to obtain a mixture includes: mixing the raw coke powder with the polar organic solvent and then stirring; optionally, the stirring time is 2 to 6 hours (e.g., 2 hours, 4 hours or 6 hours).
[0041] By stirring and mixing for a sufficient time, it can be ensured that small molecules in the coke particles that are soluble in polar organic solvents are dissolved in the polar organic solvents.
[0042] Optionally, the particle size of the raw coke powder is 1 to 100 μm (e.g., 1 μm, 10 μm, 20 μm, 50 μm, 80 μm or 100 μm).
[0043] Graphite made from raw coke powder within this particle size range exhibits good performance when used as a negative electrode, and the small molecules in the raw coke powder within this particle size range can be fully dissolved in polar organic solvents.
[0044] Optionally, the polar organic solvent is selected from at least one of tetrahydrofuran, toluene, dichloromethane, trichloromethane, and ethyl acetate.
[0045] Optionally, to ensure that small molecules in the raw coke powder are fully dissolved, the ratio of raw coke powder to polar organic solvent is 1 kg: 1 to 5 L (e.g., 1 kg: 1 L, 1 kg: 2 L or 1 kg: 5 L).
[0046] Alternatively, methods for evaporating the polar organic solvent in the mixture include:
[0047] Dry the mixture at 80–120°C (e.g., 80°C, 90°C, 100°C, or 120°C);
[0048] Alternatively, the mixture can be first subjected to rotary evaporation to recover the polar organic solvent, and then dried at 80–120°C (e.g., 80°C, 90°C, 100°C, or 120°C).
[0049] A preferred approach is to first recover the polar organic solvent by rotary evaporation of the mixture, followed by drying at 80–120°C. The recovered polar organic solvent can be reused, saving costs.
[0050] Optionally, to obtain a graphite precursor with better performance, the green coke used has an F value ≥ 0.10%, where F = M1 / M c ×100%, where M c M1 represents the mass of the raw coke. M2 represents the mass of the residue obtained after heat treatment of the solvent-soluble substance obtained from the raw coke at 500–600°C in air atmosphere following solvent extraction. The polarity parameter of the solvent used is 4.0–4.5. The solvent is selected from at least one of chloroform, ethyl acetate, and tetrahydrofuran.
[0051] The F-value can indicate the content of small molecules inside the raw coke to a certain extent. When the F-value is too small, too few organic small molecules are extracted, making it difficult to achieve the expected coating effect and resulting in poor improvement of the fast-charging performance of the graphite anode. It should be noted that for the same type of raw coke, as long as a solvent with a polarity parameter of 4.0 to 4.5 is selected for extraction and heat treatment is performed at any temperature within the range of 500 to 600℃, the measured F-values will be basically the same.
[0052] The graphite precursor provided in this embodiment of the invention is prepared using the preparation method provided in this embodiment of the invention.
[0053] The graphite preparation method provided in this embodiment of the invention involves graphitizing the graphite precursor provided in this embodiment of the invention at 2900–3100°C (e.g., 2900°C, 3000°C, or 3100°C).
[0054] The preparation method uses the graphite precursor provided in the embodiments of the present invention to prepare graphite, and the resulting graphite has better fast charging performance.
[0055] Optionally, graphitization may also include breaking down the resulting graphitized product, sieving it through a 325-mesh sieve, and obtaining the undersize material as the final product.
[0056] The graphite provided in this embodiment of the invention is prepared using the method provided in this embodiment of the invention. It exhibits superior fast-charging performance.
[0057] The negative electrode provided in this embodiment of the invention is made from the graphite provided in this embodiment of the invention.
[0058] The battery provided in this embodiment of the invention includes a negative electrode provided in this embodiment of the invention.
[0059] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0060] Example 1
[0061] 1 kg of petroleum coke powder with a particle size of 1-50 μm and an F content of 0.5% was mixed with 3 L of tetrahydrofuran and stirred for 4 h to obtain a mixture;
[0062] The mixture was first subjected to rotary evaporation under reduced pressure to allow the solvent to evaporate largely. The resulting material was then placed in a drying oven and dried at 80°C for 8 hours to allow the solvent to evaporate completely, thus obtaining the graphite precursor.
[0063] The graphite precursor was graphitized at 3000℃ for 2 hours to obtain graphite.
[0064] Comparative Example 1
[0065] This comparative example is basically the same as Example 1, except that the petroleum coke powder was not processed and was directly graphitized.
[0066] Example 2
[0067] 1 kg of needle-shaped coke powder with a particle size of 1-60 μm and F = 0.1% was mixed with 1 L of dichloromethane and stirred for 2 h to obtain a mixture;
[0068] The mixture was first subjected to rotary evaporation under reduced pressure to allow the solvent to evaporate largely. The resulting material was then placed in a drying oven and dried at 80°C for 8 hours to allow the solvent to evaporate completely, thus obtaining the graphite precursor.
[0069] The graphite precursor was graphitized at 2900℃ for 2 hours to obtain graphite.
[0070] Comparative Example 2
[0071] This comparative example is basically the same as Example 3, except that the needle-shaped coke powder was not treated and was directly graphitized.
[0072] Example 3
[0073] 1 kg of pitch coke powder with a particle size of 1-80 μm and F = 0.05% was mixed with 5 L of toluene and stirred for 6 h to obtain a mixture;
[0074] The mixture was first subjected to rotary evaporation under reduced pressure to allow the solvent to evaporate. The resulting material was then placed in a drying oven and dried at 120°C for 8 hours to allow the solvent to evaporate completely, thus obtaining the graphite precursor.
[0075] The graphite precursor was graphitized at 3100℃ for 2 hours to obtain graphite.
[0076] Comparative Example 3
[0077] This comparative example is basically the same as Example 3, except that the pitch coke was not treated and was directly graphitized.
[0078] Experimental Example
[0079] The specific surface area, degree of graphitization, and Raman spectroscopy of the graphite obtained in each embodiment and comparative example were tested:
[0080] Specific surface area testing method: The static method is used to calculate the BET specific surface area of the sample based on the nitrogen adsorption-desorption curve.
[0081] Graphitization degree testing method: X-ray diffraction test of 002 interplanar spacing, denoted as d. 002 According to the graphitization degree = (0.344 - d) 002 The result is obtained by the formula (0.344-0.3354).
[0082] Raman testing method: Raman spectrometer is used to test the Raman signal of the sample, I D / I G This is the ratio of the peak intensity of D peak to that of G peak after baseline correction.
[0083] The graphite prepared in each embodiment and comparative example was assembled into a battery, and its electrochemical performance was measured:
[0084] 1. The method for making graphite into a battery is as follows: graphite is mixed evenly with SBR, CMC and SP in a ratio of 95.5:2:1.5:1, coated on copper foil, dried and rolled to prepare electrode sheets, and assembled with lithium metal sheets to form a button cell.
[0085] 2. The specific method for electrochemical performance testing is as follows: under constant current charge and discharge conditions of 0.1C and charge and discharge voltage of 0.05 to 2.0V, the capacity and initial coulombic efficiency of the coin cell are tested; the rate performance is the ratio of the capacity at 1.2C and 0.05C currents.
[0086] Record the test results in Table 1.
[0087] Table 1. Performance tests of graphite prepared in each embodiment and comparative example.
[0088]
[0089]
[0090] As shown in Table 1, the graphite precursor prepared by the method provided in this embodiment of the invention has a slightly higher specific surface area than the graphite prepared from untreated raw coke powder, while the degree of graphitization is slightly lower. This may be attributed to the successful extraction of small molecules from the coke interior, which are then carbonized during the subsequent graphitization process, forming a disordered carbon coating layer with numerous defects and pores. The modified graphite exhibits a significantly improved 1.2C charging capacity and capacity retention, indicating that the formed disordered carbon coating layer effectively enhances the fast-charging performance of the graphite.
[0091] In summary, the method for preparing the graphite precursor provided in this invention involves treating raw coke powder with a polar organic solvent. This extracts small molecules from the raw coke that are soluble in the solvent. After the solvent evaporates, these small molecules are loaded onto the outside of the raw coke particles. Using this precursor to prepare graphite, the small molecules on the surface of the precursor are carbonized at high temperature into a non-oriented, porous hard carbon layer. This results in a graphite surface with more pores, providing ample channels for lithium-ion intercalation and effectively improving the fast-charging performance of the graphite. Furthermore, the coating material in this method is derived from the raw coke itself, achieving "self-sufficiency" and saving on coating agent costs.
[0092] The graphite precursor provided in this embodiment of the invention produces graphite with better fast-charging performance compared to untreated raw coke powder.
[0093] The graphite provided in this embodiment of the invention has better fast charging performance.
[0094] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a graphite precursor, characterized in that, include: Mix the raw coke powder with a polar organic solvent until homogeneous, and stir for 2-6 hours; The polar organic solvent in the mixture is evaporated to obtain a graphite precursor; The methods for evaporating the polar organic solvent in the mixture include: The mixture is dried at 80-120°C. Alternatively, the mixture can be first subjected to rotary evaporation to recover the polar organic solvent, and then dried at 80~120°C; The F-value of the raw coke is ≥0.1%, F=M1 / M c ×100%, where M c M1 is the mass of the raw coke, and M1 is the mass of the residue obtained by heat treatment of the substance dissolved in the solvent after solvent extraction of the raw coke at 500~600℃ in air atmosphere, with the polarity parameter of the solvent being 4.0~4.
5.
2. The preparation method according to claim 1, characterized in that, The raw coke is petroleum coke, needle coke, or pitch coke.
3. The preparation method according to claim 1, characterized in that, The particle size of raw coke powder is 1~100μm.
4. The preparation method according to claim 1, characterized in that, The polar organic solvent is selected from at least one of tetrahydrofuran, toluene, dichloromethane, trichloromethane, and ethyl acetate.
5. The preparation method according to claim 1, characterized in that, The ratio of the raw coke powder to the polar organic solvent is 1 kg: 1~5 L.
6. A graphite precursor, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 5.
7. A method for preparing graphite, characterized in that, The graphite precursor as described in claim 6 is graphitized at a temperature of 2900~3100°C.
8. A type of graphite, characterized in that, It is prepared by the preparation method described in claim 7.
9. A negative electrode, characterized in that, It is prepared using the graphite as described in claim 8.
10. A battery, characterized in that, Includes the negative electrode as described in claim 9.
Citation Information
Patent Citations
Anode active material comprising natural graphite particle with improved strength and litium secondary battery employed with the same
KR1020130058466A
Producing coated graphitic anode powders by extracting pitch from high volatile matter coke and coating the same in-situ
US20100183801A1
